Growth and Biomass Production of some Important Multipurpose Tree Species on Rainfed Sandy Loam Soils - Giri Rao, L. G.; Joseph, B.; Sreemannarayana, B. (Indian Forester, 2000)
An experiment with eleven multipurpose tree species was conducted on red sandy loam soils of Agroforestry block in Acharya NG Ranga Agricultural University, Rajendranagar campus. Evaluation of tree species nine years after plantation revealed that Dalbergia sissoo, Leucaena leucocephala, Acacia auriculiformis and Eucalyptus camaldulensis were fast growing and suitable to Southern Telengana Zone of Andhra Pradesh which are dominated with red sandy loam soil. Studies on biomass production (Small and log wood) of eleven multipurpose tree species revealed that Dalbergia sissoo (214.6 t ha-1 ) recorded maximum biomass followed by Leucaena leucocephala (187.8 t ha-1) and Acacia auriculiformis (162.4 t ha-1 ). Maximum Mean Annual Biomass Production (MABP) recorded was also more; for Dalbergia sissoo (23.8 t ha-1) followed by Leucaena leucocephala (20.9 t ha-1) and Acacia auriculiformis (18.0 t ha-1 ). Biomass yield component studies such as foliage yield at ninth year after planting revealed that maximum foliage production on oven dry weight basis was recorded by Leucaena leucocephala (16.8 t ha-1) followed by Acacia auriculiformis (12.0 t ha-1 ) and Eucalyptus camaldulensis (9.9 t ha-1 ). Cost benefit analysis of the study showed that for every rupee spent on cultivation of these tree species, highest return was obtained from Dalbergia sissoo (4.4) followed by Leucaena leucocephala (4.0), Acacia auriculiformis (3.1) and Eucalyptus (2.9).